Ancient versus modern mineral dust transported to high-altitude Alpine glaciers evidences Saharan sources and atmospheric circulation changes - Thevenon, F.; Chiaradia, M.; Adatte, T.; Hueglin, C.; Poté, J. (2018)
Mineral dust aerosols collected during the years 2008/2009 at the high-altitude research station Jungfraujoch (46°33´, 7°59´; 3580 m a.s.l.) were compared to windblown mineral dust deposited at the Colle Gnifetti glacier (45°55´ N, 7°52´ E; 4455 m a.s.l.) over the last millennium. Insoluble dust has been characterized in terms of mineralogy, Sr and Nd isotopic ratios, and trace element composition. Results demonstrate that the Saharan origin of the airborne dust did not change significantly throughout the past. Backward trajectories analysis of modern analogs furthermore confirms that major dust sources are situated in the north-central to north-western part of the Saharan desert. By contrast, less radiogenic Sr isotopic compositions are associated with lower abundances of crustal elements during low rates of dust deposition, suggesting intercontinental transport of background dust rather than activation of a secondary source. Saharan dust mobilization and meridional advection of air masses were relatively reduced during the second part of the Little Ice Age (ca. 1690–1870), except within the greatest Saharan dust event deposited around 1780–1790. Higher dust deposition with larger mean grain size and Saharan fingerprint began ca. 20 years after the industrial revolution of 1850, suggesting that increased mineral dust transport over the Alps during the last century was primarily due to drier winters in North Africa and stronger spring/summer North Atlantic southwesterlies, rather than to direct anthropogenic sources. Meanwhile, increasing carbonaceous particle emissions from fossil fuels combustion combined to higher lead enrichment factor during the last century, point to concomitant anthropogenic sources of particulate pollutants reaching high-altitude European glaciers.